2011
DOI: 10.1063/1.3598473
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic identification of reactive porphyrin motions

Abstract: Nuclear resonance vibrational spectroscopy (NRVS) reveals the vibrational dynamics of a Mössbauer probe nucleus. Here, 57 Fe NRVS measurements yield the complete spectrum of Fe vibrations in halide complexes of iron porphyrins. Iron porphine serves as a useful symmetric model for the more complex spectrum of asymmetric heme molecules that contribute to numerous essential biological processes. Quantitative comparison with the vibrational density of states (VDOS) predicted for the Fe atom by density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 88 publications
(173 reference statements)
13
36
0
Order By: Relevance
“…Peripheral substituents can have a large effect on the dynamics of the iron, especially for in-plane motions. 61, 62 In addition, we have shown that the in-plane anisotropy is related to the orientation of the axial NO in [Fe(OEP)(NO)], 64 confirming the possibility of observable anisotropy based on the first-principle calculation of NRVS. 65 …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Peripheral substituents can have a large effect on the dynamics of the iron, especially for in-plane motions. 61, 62 In addition, we have shown that the in-plane anisotropy is related to the orientation of the axial NO in [Fe(OEP)(NO)], 64 confirming the possibility of observable anisotropy based on the first-principle calculation of NRVS. 65 …”
Section: Introductionsupporting
confidence: 59%
“…In Figures 3 to 5, we compare modes in [Fe(OEP)] and [Fe(OEP)(2-MeHIm)] that involve similar atomic motions on the basis of vibrational correlational analysis. 62, 81, 82 In all illustrations the iron motion is exactly in the porphyrin plane, or nearly so, and the porphyrin plane is parallel to the page. We note that in [Fe(OEP)] the iron motion is exactly along the Fe–N p bond directions, as expected, but in [Fe(OEP)(2-MeHIm)] the motion deviates from these directions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation of ferric porphyrin halides used NRVS measurements and vibrational correlation analysis of DFT predictions to demonstrate the strong influence of peripheral substituents on the vibrational dynamics of the Fe, 76 reinforcing more qualitative observations for nitrosyl complexes. 47 Similarly, comparison with the dynamics of the smaller, more symmetric compound [Fe(P)(Im)] 77 provides a useful perspective on the more complex imidazole-ligated porphyrins considered here (see Table 3).…”
Section: Discussionmentioning
confidence: 78%
“…Second, the doming mode observed for the low-spin NO derivatives is at a higher frequency than those observed for the five-coordinate imidazole species. Observation of the doming mode at 142 cm −1 for [Fe(OEP)(Cl)] 76 suggests that the spin state may be a more important factor than ligand mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation